Non-radical degradation of organic pharmaceuticals by g-C3N4 under visible light irradiation: The overlooked role of excitonic energy transfer - Pengfei Gan; Yi Lu; Yunyi Li; Liu, Wen; Long Chen; Meiping Tong; Jialiang Liang (Journal of Hazardous Materials, 2023)
In this work, an excitonic energy transfer (EET) based non-radical mechanism was proposed for the degradation of organic pharmaceuticals by graphitic carbon nitride (g-C3N4) under visible light irradiation. Using diclofenac (DCF) as a model molecule, the competition between single electron transfer (SET) and EET was studied through modulating the exciton binding energy of g-C3N4. The different mechanisms of SET and EET for DCF degradation were predicted by DFT calculation, and further confirmed by their different degradation pathways. When EET played an important role, the rationality of some very popular radical scavengers, such as p-BQ, TEMPOL and furfuryl alcohol must be reconsidered. In addition, humic acid (HA) had a distinct effect on EET and SET. Specifically, HA enhanced the EET process through photosensitization, but suppressed SET through radical quenching effect. The effect of HA on DCF degradation depended on the contribution ratio of SET and ET.
Keywords: Energy transfer; Excitons; g-CN; Non-radical; Single electron transfer